Historical Analysis of Interactive Gamification Research: A Literature Review with Kuhn and Lakatos’ Approaches - Firmansyah, Feri Hidayatullah; Rosmansyah, Yusep; Mahayana, Dimitri (Jurnal Filsafat "WISDOM", 2024)
This literature review provides an analysis of the historical development and theoretical frameworks put forth by notable philosophers such as Thomas Kuhn and Imre Lakatos in the field of interactive gamification research. By examining the contributions and perspectives of these influential figures, the authors aimed to enhance our understanding of the evolution of gamification as a research area. This review serves as a valuable resource for individuals interested in delving deeper into the concept of gamification in interactive research. Furthermore, it offers a collection of references that can be explored in the initial stages of gamification research. By studying the works of influential philosophers such as Thomas Kuhn and Imre Lakatos, researchers can gain valuable insights into the evolution of gamification  research and its theoretical underpinnings.. Kuhn's concept of paradigm shifts and Lakatos's ideas on research programs provide researchers with a framework to understand the progression of ideas and theories within the field.